Windows Sphere: Multi-Modal Operating System Control for Disability Support using Artificial Intelligence - Sudharsanan R.; Mishra Aayush; Barua Bhuvanesi; Rane Prateek; PV Gopirajan (EPJ Web of Conferences)
Most traditional computer systems are based strongly on the standard input devices such as keyboard and mouse and they can pose a huge challenge for people with disabilities. 'Windows Sphere' is a multimodal operating system control system designed to empower individuals with disabilities through the use of artificial intelligence. Two key modules that the system integrates are: a gesture-based control module and a voice driven assistant bot F.R.I.D.A.Y. The gesture-based module allows users with partial hand functionality to operate the operating system with efficiency, thereby reducing the need for standard input devices. At the same time, F.R.I.D.A.Y., a voice recognition-based assistant, allows users without hand functionality to have seamless system control, thus enabling an offline inclusive operating experience. The system provides dual control modalities overcoming the fatigue of using a single input method by allowing additional control modalities. Additionally, the anticipated outcome of this research is a cost-effective AI driven interface that would increase accessibility and autonomy for the user however they have physical capabilities. The focus of this project is on defining a new standard for accessibility through the proposed framework, which offers great potential for extending application beyond its constraints.